2022
DOI: 10.3389/fpsyt.2022.833259
|View full text |Cite
|
Sign up to set email alerts
|

Ketamine as a prophylactic resilience-enhancing agent

Abstract: Stress exposure is one of the greatest risk factors for psychiatric illnesses, including major depressive disorder (MDD) and posttraumatic stress disorder (PTSD). Enhancing stress resilience could potentially protect against the development of stress-induced psychiatric disorders, yet no resilience-enhancing pharmaceuticals have been developed to date. This review serves to consider the existing evidence for a potential pro-resilience effect of ketamine in rodents as well as the preliminary evidence of ketamin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…The FST has predictive validity for antidepressant efficacy; generally, the time-course that antidepressants work in humans is paralleled by how these same drugs lower rodent immobility in the FST. To give some examples, selective serotonin transporter (SERT) reuptake inhibitors normalize immobility behavior when given chronically (Mukherjee et al, 2015), ketamine does this rapidly and for a period of around 2 weeks (Evers et al, 2022;Fitzgerald et al, 2019). Therefore, our findings show further evidence towards the putative antidepressant actions of reelin which expand also to the post-partum period.…”
Section: Peripheral Reelin Injectionsmentioning
confidence: 55%
“…The FST has predictive validity for antidepressant efficacy; generally, the time-course that antidepressants work in humans is paralleled by how these same drugs lower rodent immobility in the FST. To give some examples, selective serotonin transporter (SERT) reuptake inhibitors normalize immobility behavior when given chronically (Mukherjee et al, 2015), ketamine does this rapidly and for a period of around 2 weeks (Evers et al, 2022;Fitzgerald et al, 2019). Therefore, our findings show further evidence towards the putative antidepressant actions of reelin which expand also to the post-partum period.…”
Section: Peripheral Reelin Injectionsmentioning
confidence: 55%
“…Preliminary evidence in women administered with a single dose of ketamine epidurally shortly after a caesarean cut suggests that ketamine may reduce the risk of developing depressive symptoms after acute stress and postpartum depression. It has been proposed that ketamine could be used as a prophylaxis for soldiers before participation in combat [ 81 ]. The mechanism behind this effect is still unknown, but it likely involves the glutamatergic system, mesolimbic dopamine pathway, PFC, and the hippocampus, and possibly the anti-inflammatory effect of ketamine [ 81 ].…”
Section: Resultsmentioning
confidence: 99%
“…It has been proposed that ketamine could be used as a prophylaxis for soldiers before participation in combat [ 81 ]. The mechanism behind this effect is still unknown, but it likely involves the glutamatergic system, mesolimbic dopamine pathway, PFC, and the hippocampus, and possibly the anti-inflammatory effect of ketamine [ 81 ].…”
Section: Resultsmentioning
confidence: 99%
“…A similar result was observed in adults [ 25 ], implying that ketamine has the greatest impact during initial exposure to cues previously associated with aversive stimuli. In recent years, preclinical data have also shown that administering ketamine before an acute stressor can attenuate learned fear and prevent the development of PTSD-like behavior in adults [ 51 , 58 , 59 , 60 ], highlighting prophylaxis as one of the potential approaches to ketamine’s clinical application. Here, our findings show that ketamine can reduce fear in adolescents by accelerating FE, suggesting that ketamine can serve as an adjunct to ET for this age cohort.…”
Section: Discussionmentioning
confidence: 99%